Serum IL-17A and IL-6 in paediatric Mycoplasma pneumoniae pneumonia: implications for different endotypes - Heng Wang; Yanli Zhang; Chengsong Zhao; Yun Peng; Wenqi Song; Weihan Xu; Xiaohui Wen; Jinrong Liu; Haiming Yang; Ruihe Shi; Shunying Zhao (Emerging Microbes and Infections)
Paediatric Mycoplasma pneumoniae pneumonia (MPP) is a heterogeneous disease with a diverse spectrum of clinical phenotypes. No studies have demonstrated the relationship between underlying endotypes and clinical phenotypes as well as prognosis about this disease. Thus, we conducted a multicentre prospective longitudinal study on children hospitalized for MPP between June 2021 and March 2023, with the end of follow-up in August 2023. Blood samples were collected and processed at multiple time points. Multiplex cytokine assay was performed to characterize serum cytokine profiles and their dynamic changes after admission. Cluster analysis based on different clinical phenotypes was conducted. Among the included 196 patients, the levels of serum IL-17A and IL-6 showed remarkable variabilities. Four cytokine clusters based on the two cytokines and four clinical groups were identified. Significant elevation of IL-17A mainly correlated with diffuse bronchiolitis and lobar lesion by airway mucus hypersecretions, while that of IL-6 was largely associated with lobar lesion which later developed into lung necrosis. Besides, glucocorticoid therapy failed to inhibit IL-17A, and markedly elevated IL-17A and IL-6 levels may correlate with lower airway obliterans. Our study provides critical relationship between molecular signatures (endotypes) and clustered clinical phenotypes in paediatric patients with MPP.